'Agents-in-focus' and 'Agents-in-context': The strong structuration analysis of central government accounting practices and reforms in Nepal. Issue 2 (June 2017) - Adhikari, Pawan; Jayasinghe, Kelum
Abstract: Drawing on Stones' (2005) strong structuration theory, the paper unfolds why and how the key stakeholders of central government accounting in Nepal are involved in the reproduction of routinised accounting practices, resisting the externally-propagated changes. Government accountants (the agents-in-focus) through their capability to control the budget routines have enjoyed a powerful social position in their position–practice relations with the agents-in-context, i.e. professional accountants and international consultants, higher-level officers and administrators, auditors, and politicians. Social position along with historically-imbued dispositions and their conduct and context analysis have enabled government accountants to strategically exercise their agency. Government accountants have articulated duality and a dialectic relation with the agents-in-context, which have resulted in the reproduction of everyday accounting practice and the resistance to the World Bank-led reforms, such as accrual accounting and, more recently, the Cash-Basis IPSAS.